2021 38th National Radio Science Conference (NRSC) 2021
DOI: 10.1109/nrsc52299.2021.9509828
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of Respiratory System for Acute Respiratory Distress Syndrome (ARDS) Associated with COVID-19

Abstract: The respiratory system is one of the complicated systems in the human body. In this paper, the mathematical model for the respiratory system was proposed based on the electro-acoustic bio-impedance analysis with huge number of equations. Further, the behavior of each generation from 24 generations of the respiratory system can be analyzed separately. Furthermore, the pressure with ventilated frequency from 1-1200 min -1 at any generation can be predicted and calculated. The proposed mathematical model was vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Eldosoky et al ( 2021) presented a ventilator depends on its work on the Matlab program, where a large set of mathematical equations has been proposed to be implemented by the MATLAB program, and its results were accurate because all its equations were calculated directly without any assumptions. As the medical condition of the patient's respiratory system was self-diagnosed and detected by the proposed mathematical model [4].…”
Section: Nomenclature and Symbolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eldosoky et al ( 2021) presented a ventilator depends on its work on the Matlab program, where a large set of mathematical equations has been proposed to be implemented by the MATLAB program, and its results were accurate because all its equations were calculated directly without any assumptions. As the medical condition of the patient's respiratory system was self-diagnosed and detected by the proposed mathematical model [4].…”
Section: Nomenclature and Symbolsmentioning
confidence: 99%
“…Respiratory distress syndrome is one of the symptoms of coronavirus infection, as it impairs the lung's ability to exchange gases from oxygen and carbon dioxide, which causes hypoxia in blood, shortness of breath, bluish skin and thus death. Therefore, there was an urgent need to develop a mechanical breathing device in order to support the condition of patients in the intensive care unit, as well as to overcome this pandemic [4]. Where different designs and sizes of the ventilator were produced in order to compensate for the shortage of ventilators all over the world, especially during the outbreak of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide, a byproduct of cellular metabolism, can significantly affect the lungs, which may be of therapeutic importance in very unwell patients, especially those with acute respiratory distress syndrome (ARDS) (Mehrabadi et al, 2021;Awad et al, 2022). Numerous reports have shown that CO 2 may harm the lungs regardless of pH (Kacmarek et al, 2018;Pirapuraj et al, 2021).…”
Section: Icu Air Quality Monitoring and Tracking Of Harmful Volatile ...mentioning
confidence: 99%